High-Fat Diet Increased Oxidative Stress and Mitochondrial Dysfunction Induced by Renal Ischemia-Reperfusion Injury in Rat - Prem, Priyanka N.; Kurian, Gino A. (Frontiers in Physiology, 2021)
Renal ischemia-reperfusion injury is one of the major causes of acute kidney injury influenced by the ischemic duration and the presence of comorbidities. Studies have reported that high-fat diet consumption can induce renal lipotoxicity and metabolic dyshomeostasis that can compromise the kidney's vital functions. The present study evaluated the impact of a high-fat diet in the recovery of renal tissue from ischemia-reperfusion and explored the cellular pathology 24 male Wistar rats were divided into two groups: ND (normal diet; n = 12) and HD (high-fat diet; n = 12), which were further subdivided into sham and ischemia-reperfusion groups at the end of the dietary regimen. The high-fat diet was introduced in 4 weeks old rats and continued for 16 weeks. Ischemia-reperfusion (IR) was induced by bilateral clamping of the renal peduncle for 45 minutes, followed by 24 hours of reperfusion. Blood chemistry, estimated glomerular filtration rate (eGFR), mitochondrial function, and oxidative stress analysis were carried out to study the pathological changes. Rats fed with HD showed a decreased eGFR and elevated plasma creatinine, thereby compromised kidney function. Subcellular level changes in HD rats include deceased mitochondrial copy number, low PGC-1α gene expression, and declined ETC enzymes and ATP level. Upon IR induction, HD rats exhibited severely impaired renal function (eGFR-0.09 ml/min) and elevated injury markers compared with ND rats. Histological analysis displayed increased tubular necrosis and cast formation in HD-IR in comparison to ND-IR. The oxidative stress and mitochondrial dysfunction were more prominent in HD-IR. In vitro protein translation assessment revealed impaired translational capacity in HD-IR mitochondria suggests mitochondrial changes with diet that may adversely affect the outcome of IR injury. High-fat diet consumption alter the normal renal function by modifying the cellular mitochondria. The renal changes compromise the ability of the kidney to recover from ischemia during reperfusion.